2017
DOI: 10.1109/mra.2016.2636359
|View full text |Cite
|
Sign up to set email alerts
|

The STRANDS Project: Long-Term Autonomy in Everyday Environments

Abstract: Thanks to the efforts of the robotics and autonomous systems community, robots are becoming ever more capable. There is also an increasing demand from end-users for autonomous service robots that can operate in real environments for extended periods. In the STRANDS project we are tackling this demand head-on by integrating state-of-the-art artificial intelligence and robotics research into mobile service robots, and deploying these systems for long-term installations in security and care environments. Over fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
134
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 14 publications
0
134
0
Order By: Relevance
“…Further, we collect data at the viewpoints computed and we extract one object model for each experiment. 1 We compare our results qualitatively with the results obtained by [2], where a mobile robot was used to acquire views and build models of the objects autonomously. Two types of experiments were performed in [2]: controlled and uncontrolled.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Further, we collect data at the viewpoints computed and we extract one object model for each experiment. 1 We compare our results qualitatively with the results obtained by [2], where a mobile robot was used to acquire views and build models of the objects autonomously. Two types of experiments were performed in [2]: controlled and uncontrolled.…”
Section: Resultsmentioning
confidence: 80%
“…[1] report deploying mobile robots in unstructured environments (offices and elderly care homes) for durations of up to 6 months. Such experiments are pushing the boundaries of what these systems are capable of, and widen the frontier to the next set of issues to be addressed, such as exposure to large amounts of data, learning patterns about the environment, life-long robust localization and navigation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Results of survey papers from participants, including four statements with Likert-scale responses.on average. Despite the quantitative improvements, there was no significant difference observed from the scores collected from the survey prompts 2. …”
mentioning
confidence: 83%
“…Advances in autonomous robotics are gradually enabling deployment of robots in human-populated environments [1]. Human activity tends to cause changes to the environments it takes place in, and the mobile robots that share these environments need to be able to cope with such never-ending changes.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have shown that even simple models of the environment that adapt to changes improve the overall ability of mobile robots to operate over longer time periods [2], [3], [4], [5], [6]. Moreover, the ability of long-term autonomous operation improves the chances of observing the temporal changes, and thus to extract more valuable information about the environment dynamics, resulting in more accurate spatio-temporal models [1].…”
Section: Introductionmentioning
confidence: 99%